The Relationship between Foreign Direct Investment and Local Economic Growth: A Case Study of Binh Dinh Province, Vietnam - Lê Bảo; Ngô Thị Thanh Thuý; Nguyễn Ngọc Tiến; Nguyễn Duy Thục (My University, 2021)
The Relationship between Foreign Direct Investment and Local Economic Growth: A Case Study of Binh Dinh Province, Vietnam
Keywords: FDI; Economic Growth; Binh Dinh